О номенклатуре, синонимике, диффернциальном диагнозе и распространении Aedes (Ochlerotatus) albineus Seguy (Diptera, Culicidae) - Данилов, В.Н. (Вестник зоологии, 1979)
The denomination Aedes (Ochlerotatus) albineus Seguy, 1923 for mosquitos of the Northern Africa is rehabilitated as a species one and A. (O.) stramineus Dubitzky, 1970 becomes its synonym for mosquitos from Kazakhstan, southern Siberia and from Mongolia and A. (O.) flavidorsalis Luh et Lee, 1975 becomes the synonym for mosquitos from the Central China. Certain characters are found permitting A. albineus to be differentiated from other species of the A. caspius group in the Eastern Palearctic (A. caspius, A. dorsalis, A. campestris) by males genitals, larvae of age IV and claws of female tarsus. A. albineus distribution is shown. Geographical variability of 5—C hairs branching and occurrence of branched 6—C hairs in larvae of this species is studied.